Muscle fascicle length adaptations to high-velocity training in young adults with cerebral palsy - Gallinger, Tessa L.; MacIntosh, Brian R.; Fletcher, Jared R. (Frontiers in Sports and Active Living, 2025)
IntroductionIn individuals with Cerebral Palsy (CP), both muscle cross-sectional area and fascicle length are reduced, contributing to decreased muscle strength, muscle shortening velocity and muscle mechanical power output, particularly in the plantarflexor muscles. A proposed mechanism to target increased muscle mechanical power output is to incorporate high velocity training (HVT) in these individuals, to increase fascicle length via sarcomerogenesis. To determine the effects of HVT on changes in MG muscle fascicle length and that impact on changes to MG muscle force-length-velocity-power characteristics in young adults with CP.Methods12 young adults with CP (GMFCS I or II, 22.8 ± 6.0 years) were randomly allocated (some crossover) to no training (CP-NT, n = 8), or training (CP-T, n = 8). 10 recreationally trained healthy adults (HA, 22.5 ± 2.8 years) served as controls. CP-T performed 10-week training of biweekly sessions consisting of progressive intensity 10 m sprints, plyometrics and agility tasks. Triceps surae muscle force-power-velocity relationships were quantified with isokinetic dynamometry and ultrasound imaging. Data are expressed relative to pre-intervention values.ResultsHVT resulted in a significant increase in fascicle length in CP-T (+1.92 ± 3.21 mm, p < 0.005) compared to a significant decrease in CP-NT (−1.63 ± 3.00 mm, p < 0.013). While HVT did not result in significant changes in maximal shortening velocity (Vmax) or maximal peak power output (Pmax), a large effect size for vmax following training in CP-T was seen (+45.2 ± 76.4%, d = 0.909, p = 0.452), in contrast to CP-NT (+2.9 ± 70.5%, d = 0.059, p = 1.00). HVT also resulted in a very large effect for Pmax in CP-T (+35.0 ± 49.1%, d = 1.093, p = 0.232), but only a small effect was observed in CP-NT (+7.8 ± 49.1%, d = 0.245, p = 1.00). HA had significantly greater Pmax (p < 0.001), longer resting and active fascicle lengths (p < 0.001) and greater muscle force (p < 0.001), compared to CP-T.DiscussionHVT is a feasible training intervention to increase triceps surae muscle fascicle length in individuals with CP. HVT can partially mitigate losses in Pmax in CP compared to healthy adults. Longer HVT programs may be required to increase muscle mechanical power output in CP to levels observed in HA.